The content of total protein and its fractions in the hemolymph and body tis-sues of bees fed with Mg citrate - I. I. Kovalchuk; R. L. Androshulik; A. Z. Pylypets; M. M. Tsap (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Mineral elements increase the capacity of organisms for their adaptation to abiotic factors and improve the biological value of animal products. The aim of the experiment was to study the effect of magnesium citrate on the content of total protein in the tissues of the whole organism, the content of soluble protein fractions in hemolymph, and catalase activity. The research was conducted on Carpathian honey bees. They were selected in the apiary at the Institute of Animal Biology of the National Academy of Sciences. The research was conducted in two stages. The first stage of the work was carried out on 5 groups of bees under the conditions of a laboratory thermostat for 20 days. Bees of the control group were fed daily with 1 ml of 50 % sugar syrup (SS) and 1 ml of H2O; group II – 1 ml of SS + 1 ml of 0.4 mg Mg/l nanocitrate; group III – 1 ml of CS + 1 ml of 2 mg Mg/l citrate; group IV – 1 ml of SS + 1 ml of 3 mg Mg/l citrate; group V – 1 ml of SS + 1 ml of 4 mg Mg/l citrate. The second stage of the study was conducted on four groups of bees and lasted 30 days. Bees of the control (I) group were fed daily with 1 ml of 50 % SS and 1 ml of H2O; group II – 1 ml of SS + 1 ml of 0.04 mg Mg/l citrate; group III – 1 ml of SS + 1 ml of 0.02 mg Mg/l citrate; group IV – 1 ml of SS + 1 ml of 0.01 mg Mg/l citrate. At the first stage, a decrease in α1-globulins in the hemolymph of bees of the III – V groups was established. The content of β-globulins increased in the II (P < 0.001), III (P < 0.01), IV (P < 0.001) and V (P < 0.001) experimental groups. The content of γ-globulins decreased in hemolymph of II (P < 0.001) and III (P < 0.01) groups. At the second stage, a decrease in α1–globulins was observed in the hemolymph of bees of the II, III and IV experimental groups compared to the control. The content of α2-globulins was significantly lower in the hemolymph of bees from IV group, and the content of β-globulins was higher in the hemolymph of the bees. An increase in the content of γ-globulins was established in II (P < 0.05), III and IV (P < 0.01) experimental groups. High catalase activity was observed in the hemolymph of bees of all experimental groups (P < 0.001). The highest catalase activity was registered in bees of IV group. The use of 0.01 mg of Mg citrate in addition to sugar syrup feeding changed the ratio of individual hemolymph protein fractions. The relative content of albumin and β-globulin decreased and α2 and γ globulin content increased. An increase in the relative content of α1 and a decrease in β- and γ-globulins in the hemolymph of honey bees of the research groups were caused by Mg citrate in a dose of 0.04 mg.